Religious Culture Leadership of Islamic Boarding School in Improving The Quality of Education in Wahidiyah Islamic Boarding School Kedunglo Bandar Lor and Wali Barokah LDII Burengan in Kediri City - Khoiruddin, Untung; Zuhdi, Muhammad (Didaktika Religia, 2019)
Religious culture of pesantren has its uniqueness which is still expected to be a support for the development of the education system in Indonesia. The authenticity and distinctiveness of the pesantren as well as the treasure the nation’s cultural traditions, is also a butter force for the educational pillar to bring up moral leaders of the nation, is a form of pesantren education that is characterized by traditionalism. This study used a qualitative approach. The data were collected through observations, interviews, and content analysis. The process of improving the quality of pesantren education is part of the development of national education, which is part of an effort to improve the quality of full human education. For achieving the quality of education, it must be based on a significant change. The change is needed in the management of quality and competitive educational institutions. Now one of the challenges faced by educational institutions is how to manage quality. Quality educational institutions, institutions that prioritize the quality of graduates and are able to demonstrate the values of education that make a top priority, due to a significant change in pesantren.